SROI Self-assessment tool (SROI Network, 2016)
The online self assessment tool was created by the SROI Network in collaboration with Hall Aitken to help users judge how well their evaluation practices adhere to principles of best practice. The tool is comprised of a seven stage questionnaire, showing results as a spider chart illustrating areas of strength and areas for improvement. The questionnaire itself is structured around the seven principles of SROI. These principles include ‘involve stakeholders’, ‘be transparent’ and ‘do not overclaim’, and together make up the core framework around which SROI is based. Users receive a score for each principle, and an overall average, giving them an idea of to what extent they have successfully applied the principles. High scoring users can then use their score to guide them towards applying for assurance and accreditation. The tool provides guidance, support and more advice to people who want to improve the way in which their organisation measures their social value and assesses their service delivery but don’t know where to start.